PENGARUH KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PT. ELANG MAHKOTA TEKNOLOGI, Tbk. PERIODE 2012-2022 - Manggali, Retno Mas Pinkan; Trisnia Widuri; Kukuh Harianto (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
ABSTRACT This study examines the differences in financial performance before and after the acquisition at PT. Elang Mahkota Teknologi Tbk. for the period 2012-2022. Using the financial ratios of current ratio, earning per share, total asset turnover, and debt to asset ratio. This study uses the one sample kolmogorov-smirnov normality test method and paired samples t-test. The results of the study were that the current ratio, earning per share, total asset turnover, and debt to asset ratio did not differ significantly between before and after the acquisition. The company should reconsider its decision more carefully through an analysis of the financial statements and the performance and financial conditions of the target company. This is important considering the high risks associated with the acquisition. Based on this study, it was found that the company did not experience a significant difference in financial performance before and after the acquisition, as seen from the financial ratio. For further research, it is recommended to add variations in financial ratios as research variables that can affect the company's financial performance. Keywords: Financial Performance, Aquisition